Pedagogical specialised lexicography: the representation of meaning in English and Spanish business dictionaries - Fuertes Olivera, Pedro Antonio (Terminology and lexicography research and practice, 2008)
This stimulating new book, which combines dictionary research and linguistic knowledge, analyses the representation of meaning in business dictionaries from a pedagogical perspective. By examining in detail the macrostructure, mediostructure, access structure and microstructure of eight business dictionaries, this book presents interesting findings on how the dictionaries studied represent the 'noun-term', and on how they cope with the principles of new lexicography that aims at solving the needs of a specific type of user with specific types of problems related to a specific type of user situ.